Association between household food security and socioeconomic status with paternal smoking: Findings from SEANUTS II Malaysia - Giin Shang Yeo; Shoo Thien Lee; Kuan Chiet Teh; Jyh Eiin Wong; Wan Siti Fatimah Wan Abdul Rahman; Nurul Hasanah Hasmuni Chew; Caryn Mei Hsien Chan; Nur Zakiah Mohd Saat; Nik Shanita Safii; Siti Balkis Budin; Swee Fong Tang; A. Karim Norimah; et al. (PLoS ONE, 2026)
Individuals burdened with socioeconomic disadvantages, including food insecurity, are often exposed to circumstances that may increase the likelihood of smoking, which may in turn affect the respiratory health of others in the household, particularly children. Yet, the role of these factors in perpetuating tobacco use within households remains underexplored. Therefore, this study attempts to determine the association between household food security and socioeconomic status with paternal smoking in Malaysia. This study utilised data from the South East Asian Nutrition Surveys (SEANUTS II) Malaysia, which involved 2,687 children aged 0.5–12.9 years, recruited through multistage cluster sampling. Although the study recruited children as participants, the present analysis draws on paternal and household information, including food security, socioeconomic status, and paternal smoking, as reported through parent/guardian-reported questionnaires. Multivariate binary logistic regression was used to determine factors associated with paternal smoking habits. Overall, forty-three percent of fathers were reported as smokers. Younger fathers (aged <30.0 years) had twice the odds of smoking [aOR: 2.032 (95%CI 1.301–3.173)] compared to their older counterparts (aged >49.9 years). Fathers from low socioeconomic status households, particularly, those with extremely low household income [aOR: 2.606 (95%CI 1.711–3.968)] and without formal education/completed primary education [aOR: 2.604 (95%CI 1.710–3.966)], had double the odds of smoking than their counterparts. Self-employed/other occupation fathers [aOR: 1.343 (95%CI 1.056–1.709)] and families from food-insecure households [aOR: 1.251 (95%CI 1.053–1.487)] were found to have higher odds of smoking. In conclusion, household food insecurity and socioeconomic status, including age, occupation, household income, and education level were significantly associated with paternal smoking status. Authorities should customise interventions to mitigate socioeconomic barriers and create equitable access to quit-smoking resources. This is important for lowering smoking prevalence and safeguarding children’s health.